2016
DOI: 10.1016/j.wombi.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Birthplace as the midwife's work place: How does place of birth impact on midwives?

Abstract: Given the excellent outcomes of midwifery led care, we should focus on how we can facilitate the work of midwives in all settings. This study suggests that the culture of the birthplace rather than the physicality is the highest priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 29 publications
2
65
0
Order By: Relevance
“…The results presented here are in line with other findings about opposing models that guide childbirth care in hospitals (Blaaka & Schauer Eri, 2008;Davis & Homer, 2016;Hunter, 2004;Olafsdottir, 2006Olafsdottir, /2011. Being in this field of tension can also be related to the different perspectives and the dominance of the medical/technocratic vs. social/midwifery models of childbirth care (Bryar & Sinclair, 2011;Davis-Floyd, 2003;Hunter, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results presented here are in line with other findings about opposing models that guide childbirth care in hospitals (Blaaka & Schauer Eri, 2008;Davis & Homer, 2016;Hunter, 2004;Olafsdottir, 2006Olafsdottir, /2011. Being in this field of tension can also be related to the different perspectives and the dominance of the medical/technocratic vs. social/midwifery models of childbirth care (Bryar & Sinclair, 2011;Davis-Floyd, 2003;Hunter, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…They considered such care to be "real midwifery" and was described in a metasynthesis of midwifery care (O'Connell & Downe, 2009) as an overly "idealized" approach that is difficult to attain in hospital labour ward settings. In addition, the midwives' ambivalence to the birthing rooms and the office could be an expression of powerful social norms in hospital labour wards that have been identified as appearing busy, while doing "busy work" (Davis & Homer, 2016), instead of being with the women in the birthing rooms (Hunter, 2004(Hunter, , 2002, which has also been described as "vigilant attendance" and "the art of doing 'nothing' well" (Kennedy, 2000). A birthing culture with an overly reductionist perspective could result in obstetrical mistreatment (Bohren et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with those of 3 studies (Freeman et al, 2006;Priddis et al, 2012;Davis and Homer, 2016) that found maternal position to be influenced by other factors, including delivery room equipment, the midwife's practices and experience, and place of work. Their experience also appears to affect their practices, since those in practice for the fewest years offered the most alternatives to an epidural analgesic as well as a wider range of positions.…”
Section: Discussionsupporting
confidence: 91%
“…Within maternity services, several studies have documented midwifery workplace culture and identified a range of potential problems (Arundell, Mannix, Sheehan, & Peters, ; Ball, Curtis, & Kirkham, ; Catling, Reid, & Hunter, ; Cummins, Catling, Hogan, & Homer, ; Curtis, Ball, & Kirkham, ; Davis & Homer, ; Farrell & Shafiei, ; Pezaro, Clyne, Turner, Fulton, & Gerada, ). Issues such as low morale and inappropriate workplace behaviour, including bullying, may impact on midwives' capacity to care for women and newborn infants.…”
Section: Introductionmentioning
confidence: 99%